Severe head injuries in three countries. Issue 3 (March 1977) - Jennett, B; Teasdale, G; Galbraith, S; Pickard, J; Grant, H; Braakman, R; Avezaat, C; Maas, A; Minderhoud, J; Vecht, C J; Heiden, J; Small, R; et al.
Abstract : Methods for assessing early characteristics and late outcome after severe head injury have been devised and applied to 700 cases in three countries (Scotland, Netherlands, and USA). There was a close similarity between the initial features of patients in the three series; in spite of differences on organisation of care and in details of management, the mortality was exactly the same in each country. This data bank of cases (which is still being enlarged) can be used for predicting outcome in new cases, and for setting up trials of management.